2014
DOI: 10.1136/bcr-2014-011181
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular coil retrieval using a TrevoProVue stentriever

Abstract: A 65-year-old man with a left cavernous internal carotid artery cerebral aneurysm experienced a premature detachment of the first framing coil (10 mm×40 cm Penumbra Complex Standard) during a coil embolization procedure. The coil herniated into the anterior cerebral artery and pericallosal artery. Multiple attempts to retrieve the coil using both a 2 and 4 mm Microsnare (Amplatz GooseNeck) failed. A Trevo ProVue retrievable stent was then used to retrieve the coil without any adverse events. This case report h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Successes using a second stent retriever device to capture the detached stent have been reported [22]. A novel use of the Trevo device in foreign-body recovery of migrated coils is also described [24,25]. However, the risk-benefit profile of such a technique must be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Successes using a second stent retriever device to capture the detached stent have been reported [22]. A novel use of the Trevo device in foreign-body recovery of migrated coils is also described [24,25]. However, the risk-benefit profile of such a technique must be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…While all published cases dealt with intracranial coils (3)(4)(5)(6)8) and only one case with a dislocated coil in the peroneal artery ( 9), we have shown that retrieving dislocated coils in the abdominal vessels is also effective and this time using yet another available stent retriever (pRESET). To our knowledge is this case study the rst one to deal with a coil dislocation in an abdominal vessel and the rst one to use the pRESET stent retriever.…”
Section: Discussionmentioning
confidence: 85%
“…Recovery of dislocated coils with stent retrievers has been reported with various stent retrievers, including Solitaire (Medtronic, Minnesota, USA), Trevo (Stryker, Kalamazoo, MI) and Catch device (Balt, Montmorency, France). This method has proven to be highly effective in a few already published studies and case reports (3)(4)(5)(6)8).…”
Section: Discussionmentioning
confidence: 98%
“…There have been limited reports of the successful use of various devices for retrieving a coil that has migrated or become misplaced, including the Microsnare (15), a microcatheter retriever (Retriever-10 and Retriever-18), the Alligator Retrieval Device (9,15), Merci retriever (16), the Solitaire™ AB stent retriever (10) and the Trevo Stentriever device (11,17). Several experts have shaped microwires to capture migrated coils (18,19); however, the majority of clinicians use one of the following four types of coil retrieval devices: Snares, clamps, stents or spiral devices.…”
Section: Discussionmentioning
confidence: 99%